Nuclear energy density functionals constrained by low-energy QCD - Vretenar, D. (HNPS Advances in Nuclear Physics, 2020)
Relativistic nuclear energy density functionals are formulated and developed, guided by two important features that establish connections with chiral dynamics and the sym- metry breaking pattern of low-energy QCD: a) strong scalar and vector fields related to in-medium changes of QCD vacuum condensates; b) the long- and intermediate-range interactions generated by one-and two-pion exchange, derived from in-medium chiral per- turbation theory.